2022
DOI: 10.3389/fimmu.2022.875488
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term and Short-Term Efficacy of Immunotherapy in Non-Small Cell Lung Cancer Patients With Brain Metastases: A Systematic Review and Meta-Analysis

Abstract: BackgroundAlthough immunotherapy has been widely used, there is currently no research comparing immunotherapy for non-small cell lung cancer (NSCLC) patients with brain metastases (BMs). This meta-analysis addresses a gap in the comparison of immunotherapy efficacy, including immune checkpoint inhibitors (ICIs), chemotherapy (CT), radiotherapy (RT), and ICI combined CT or RT.MethodsA search of Pubmed, Cochrane, EMBASE, and ClinicalTrial.gov was conducted to identify studies which enrolled NSCLC patients with B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 94 publications
0
11
0
Order By: Relevance
“…A phase 2 prospective study suggested that a PD-1 inhibitor had CNS efficacy, with an intracranial ORR of 29.7% and PFS of 2.3 months in PD-L1-positive NSCLC patients with untreated BMs (16). Moreover, a series of retrospective studies have reported superior CNS efficacy of ICI therapy compared to ICI-naĂŻve therapy (29)(30)(31). Nevertheless, the vast majority of patients in these studies have wild-type EGFR, and data regarding the intracranial efficacy of ICI therapy in patients with EGFR mutations with BMs are rare.…”
Section: Discussionmentioning
confidence: 99%
“…A phase 2 prospective study suggested that a PD-1 inhibitor had CNS efficacy, with an intracranial ORR of 29.7% and PFS of 2.3 months in PD-L1-positive NSCLC patients with untreated BMs (16). Moreover, a series of retrospective studies have reported superior CNS efficacy of ICI therapy compared to ICI-naĂŻve therapy (29)(30)(31). Nevertheless, the vast majority of patients in these studies have wild-type EGFR, and data regarding the intracranial efficacy of ICI therapy in patients with EGFR mutations with BMs are rare.…”
Section: Discussionmentioning
confidence: 99%
“…There has been no established definition for 'long-term PFS' in anticancer chemotherapy, and it varies by therapy (15)(16)(17)(18). Most of the reported 'long-term PFS' are PFS for first-line chemotherapy, and 'long-term PFS' is rarely used in second-line and subsequent treatments (19).…”
Section: Definition Of Long-term Pfs For Doc+rammentioning
confidence: 99%
“…Also, several meta-analyses support that ICI monotherapy is efficacious for metastatic brain tumors [ 7 , 8 ]. However, in the included studies of these meta-analyses, only patients with treatment-naĂŻve metastases were enrolled, and the vast majority of prospective studies excluded patients with symptomatic brain metastases [ 7 , 8 ]. Yet, only 20% of the patients benefited from immunotherapy [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, in the included studies of these meta-analyses, only patients with treatment-naĂŻve metastases were enrolled, and the vast majority of prospective studies excluded patients with symptomatic brain metastases [ 7 , 8 ]. Yet, only 20% of the patients benefited from immunotherapy [ 7 ]. The efficacy of ICIs for other patients needs further investigation.…”
Section: Introductionmentioning
confidence: 99%